Implementing Used Cooking Oil to Soap Conversion and Digital Marketing in PKK RW 14 Sekeloa Bandung Indonesia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Community members often dispose of used cooking oil into drains, which harms local environments and misses a simple valorization pathway. This program with PKK RW 14 Sekeloa in Bandung trained 15 participants to convert used oil into household bar soap and to operate basic digital selling routines. A one-group pre and post evaluation used 5 instruments: soap-making knowledge and attitudes (5 items), behavior and readiness to adopt soap-making (5 items), post-only perceived impact and sustainability (5 items), technology use for listing and operations (19 items), and a 10-item knowledge quiz. Results show consistent improvement. On knowledge and attitudes, the largest item gain was basic soap-making steps (+40 percentage points, favorable 40% to 80%); basic processing method and economic potential increased by +27 points each, raising favorable to 93% and 80%. Item averages moved from 55% to 81% favorable. On behavior and readiness, improper disposal (reverse-scored) improved by +60 points to 93% favorable, while item averages rose from 55% to 79% favorable. Post-only perceptions were strongly positive (85% favorable on average; usefulness and environmental awareness 93% each). Technology use advanced broadly from 32% to 75% favorable on item averages, with many domains at 73-93% favorable after training; promotions and cost recording remained the weakest areas. Quiz scores improved from 6.0 ± 1.3 to 8.9 ± 0.8, with participants scoring ≥8/10 increasing from 33% to 87%. The findings indicate that a short, safety-focused curriculum coupled with simple operating standards can build procedural competence and immediate readiness for micro-enterprises and its replicability in other urban communities.